Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1109/tnsre.2003.810559
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for improving neural signal detection using a neural-electronic interface

Abstract: Abstract-There have been various theoretical and experi mental studies presented in the literature that focus on interfacing neurons with discrete electronic devices, such as transistors. From both a theoretical and experimental perspective, these studies have emphasized the variability in the characteristics of the detected action potential from the nerve cell. The demonstrated lack of reproducible fidelity of the nerve cell action potential at the device junction would make it impractical to implement these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…A large number of factors can take part in the generation and propagation of action potential, such as: external stimulus [1], noise (internal or external) [2,3], specific ion channels [4], membrane capacitance [5], and temperatures [6], etc. Membrane capacitance (C m ) as one of the factors may be defined as:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of factors can take part in the generation and propagation of action potential, such as: external stimulus [1], noise (internal or external) [2,3], specific ion channels [4], membrane capacitance [5], and temperatures [6], etc. Membrane capacitance (C m ) as one of the factors may be defined as:…”
Section: Introductionmentioning
confidence: 99%
“…Amzica et al [27] investigated the role of membrane capacitance in sleep oscillations and spike-wave seizures. Szlavik [5] gave a detailed analysis of the impact of variations in membrane capacitance on the detected neuralelectronic signal, and concluded that larger values of membrane capacitance results in smaller initial changes in potential across the cell membrane, while smaller values of membrane capacitance yield larger initial changes in transmembrane potential that can be sufficient to generate an action potential. These studies are helpful and instructive, but seldom discussed the exact role of C m in burst firing patterns, especially the transitions among these patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies include simulations of neural detection using synthetic electronic circuitry [2], [3]. Additional studies include simulations of neural excitation using external electronics [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…The simplicity of the overall circuit topology is a common feature of the simulations pre sented in the above literature. The approach adopted in some of these studies involves solution of the circuit equations using conventional numerical ordinary differential equation solvers or circuit simulation software [3], [5]- [7]. Algebraic manip ulation involves rewriting these equations in a form whereby the first derivatives are isolated on one side.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling approach adopted in this study is analogous to the approach taken in Szlavik [5]. The physical parameters related to the membrane and the transistor are shown in Table 1., along with the definition of the circuit components.…”
Section: Methodsmentioning
confidence: 99%